The structure influences of the stress state on straining non-corrosive steel during the additional impulse charges - Chausov, N. H.; Pilipenko, A. P.; Berezin, V. B.; Paratsa, V. N.; Luchko, I. I. (Science and Transport Progress, 2011)
Features of the dissipative structure formation in stainless steel under complex loading mode - static tension with impulse strain increase and bending are shown.